Service Quality, Brand Attributes, Satisfaction and Loyalty of Guests Staying at Le Meridien Hotel Bali Jimbaran - Dewi, Luh Putu Triyanti Ariestiana; Wiranatha, Agung Suryawan; Suryawardani, I Gusti Ayu Oka (E-Journal of Tourism; Volume 8 Number 1 (March 2021)DO - 10.24922/eot.v8i1.71451, 2021)
Guest satisfaction and loyalty become an indicator of the success of a hotel. Service quality and brand attributes are two components that related the satisfaction and loyalty of guests who stay at the hotel. The purposes of this study were 1) To analyse the relationship of service quality and brand attributes to the satisfaction of guests staying at the Le Meridien Bali Jimbaran hotel, 2) To analyse the relationships of service quality and brand attributes to the loyalty of guests staying at the Le Meridien Bali Jimbaran hotel, 3) To analyse the satisfaction of the guests staying at the Le Meridien Bali Jimbaran hotel. This research used quantitative method involving 100 guests who stayed overnight as the respondents. Sampling was done by accidental sampling and analysis using Structural Equation Model (SEM) with SmartPLS 3.0 software. The results showed that 1) Service quality had a significant effect on satisfaction, 2) Service quality had no significant effect on loyalty, 3) Brand attributes had a significant effect on satisfaction, 4) Brand attributes had significant influence on loyalty, and 5) Satisfaction has a significant effect on loyalty. Suggestions that can be made in this study that hotel should support loyalty, maintain and pay close attention to brand attributes that need to be improved and guest mindset influence, as well as the should find other aspects that can support and increase guest loyalty.